Future Primary School Teachers’ Conceptions About Parents’ Participation in School - Cárcamo-Vásquez, Héctor (2023)
Purpose. This article aims to unveil future elementary education teachers’ conceptions of parents’ participation in school. Method. From a qualitative approach, the study was conducted in four universities in the Ñuble and Bío Bío regions in Chile. The data were collected through semi-structured interviews with 40 elementary education students. The discourses were analyzed using the semantic structural analysis technique. Results. As main findings, a whole of beliefs can be pointed out, from which parental participation is valued in the way it contributes to achieving academic objectives, both in terms of attitudinal modeling and reinforcement of curricular content. From there, the prevailing conception is grasped, which places participation as an indicator of parental commitment as long as it does not interfere with the work of the teaching staff. Conclusions. The need to incorporate the theme from the initial training of teachers is evidenced and to recognize the diversity of family models and strategies that guide the performance of the educational and parental role.